Interrelationships of work-family conflict, conflict with mother-in-law, dyadic coping, marital satisfaction, and marital stability among Malaysian Chinese dual-earner couples - Leong, Mei San (2021)
Managing both work and family simultaneously is a tough responsibility. However, many past studies that investigated such issue were conducted in Western countries. The objective of this thesis is to examine how marital satisfaction is experienced by both spouses should they face work-family conflict and conflict with mother-in-law, while considering other personal factors of gender role attitudes and dyadic coping. The Vulnerability-Stress-Adaptation Model of Marriage, Social Role Theory, and Role Conflict Theory were used to guide the present study in explaining the relationships between gender role attitudes, work-family conflict, conflict with mother-in-law, dyadic coping, marital satisfaction and marital stability among Malaysian Chinese dual-earner couples. Work-family conflict in this study is bidirectional which includes work interfering with family (WIF) and family interfering with work (FIW). The second objective of this thesis is on the spillover and crossover effects of work-family conflict and dyadic coping on the family outcome of marital satisfaction. Concerning how dual-earner couples cope with the stressors faced (work-family conflict and conflict with mother-in-law), the third objective focuses on the mediating role of dyadic coping towards the relationship between the stressors and marital satisfaction. An exploratory research design was used to investigate this issue by collecting dyadic data from 134 Malaysian Chinese dual-earner couples (268 individuals) aged between 27 to 61 years old. The participants completed the survey, which was a combination of instruments measuring the latent variables of gender role attitude, work-family conflict, conflict with mother-in-law, dyadic coping, marital satisfaction, marital stability, and a brief demographic data. The research hypotheses were tested using Partial Least Square (PLS) Structural Equation Modeling. The results showed that the husband’s and wife’s WIF (rs = -0.244, p = .002 [husband]; rs = -0.158, p = .034 [wife]), FIW (rs = - 0.200, p = .010 [husband]; rs = -0.224, p = .005 [wife]) and dyadic coping (rs = 0.512, p = .000 [husband]; rs = 0.596, p = .000 [wife]) were significantly correlated to marital satisfaction. Conversely, gender role attitudes and conflict with mother-in-law were not significantly correlated to marital satisfaction. The overall model of gender role attitudes, WIF, and dyadic coping explained 35.8% variance of marital satisfaction. The second overall model of gender role attitudes, FIW, and dyadic coping explained 35.3% variance of marital satisfaction. The third model of gender role attitudes, conflict with mother-in-law, and dyadic coping explained 35.4% variance of marital satisfaction. No significant gender differences were found in all variables. The spillover effects of WIF, FIW, and dyadic coping were also significant for husbands’ WIF (ꞵ = - 0.286, p = .000), FIW (ꞵ = -0.249, p = .005), dyadic coping (ꞵ = 0.456, p = .000), wives’ FIW (ꞵ = -0.248, p = .003), and dyadic coping (ꞵ = 0.581, p = .000) to their own marital satisfaction. Only one crossover effect of husbands’ WIF conflict (ꞵ = -0.180, p = .019) was significant. The actor effect of dyadic coping significantly mediates the relationship between husband’s WIF and marital satisfaction (ꞵ = - 0.106, p = .022), husband’s and wife’s FIW and marital satisfaction (ꞵ = -0.152, p = .008 [husband]; ꞵ = -0.113, p = .015 [wife]), husband’s conflict with mother-in-law and marital satisfaction (ꞵ = -0.146, p = .007). This study contributes to the understanding of the spillover and crossover effects of work-family conflict and dyadic coping to marital satisfaction among Malaysian Chinese dual-earner couples. Furthermore, the role of dyadic coping and how it mediates the relationship between stressors and marital satisfaction are highlighted. The theories are supported, and better coping skills significantly lead to a higher level of marital satisfaction among the participants. Thus, psychoeducational programs may need to consider educating couples on how to cope with life stressors in order to enhance marital satisfaction. This may be the first study done among Malaysian Chinese that collected dyadic data. The findings of this study allow comparison between spouses and it signifies cross-cultural comparisons on how work-family conflict is experienced in different cultures for future studies.